2007
DOI: 10.1099/vir.0.82563-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies specific to the HA2 glycopolypeptide of influenza A virus haemagglutinin with fusion-inhibition activity contribute to the protection of mice against lethal infection

Abstract: Four monoclonal antibodies (mAbs) recognizing distinct antigenic sites on the HA2 glycopolypeptide of influenza virus A/Dunedin/4/73 (H3N2) have been tested for in vivo protection. When applied intravenously before infection, three of them increased the survival of BALB/c mice infected with 1 LD 50 homologous virus. The protection resulted simultaneously in 2 days earlier clearance of virus from the lungs. These three antibodies inhibited the fusion activity of virus in previous in vitro experiments. One of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 27 publications
(18 reference statements)
4
54
0
Order By: Relevance
“…HA2 gp is a relatively conserved protein, and some HA2 epitopes are even shared among HA subtypes (Kostolanský et al, 2002;Varečková et al, 2008). HA2-specific antibodies recognizing HA stem were shown to be protective (Gocník et al, 2007(Gocník et al, , 2008Prabhu et al, 2009;Sui et al, 2009;Wang et al, 2010;Staneková et al, 2011;Janulíková et al, 2012), though they do not mediate virus neutralization by blocking the receptor-binding site on HA. We therefore suggest that anti-stem HA antibodies could help individuals exposed to dangerous avian IAV to overcome the infection in a subclinical manner.…”
Section: Discussionmentioning
confidence: 99%
“…HA2 gp is a relatively conserved protein, and some HA2 epitopes are even shared among HA subtypes (Kostolanský et al, 2002;Varečková et al, 2008). HA2-specific antibodies recognizing HA stem were shown to be protective (Gocník et al, 2007(Gocník et al, , 2008Prabhu et al, 2009;Sui et al, 2009;Wang et al, 2010;Staneková et al, 2011;Janulíková et al, 2012), though they do not mediate virus neutralization by blocking the receptor-binding site on HA. We therefore suggest that anti-stem HA antibodies could help individuals exposed to dangerous avian IAV to overcome the infection in a subclinical manner.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies we have shown that MAbs specific to hA2 gp, which are cross-reactive with different virus subtypes, inhibit the fusion activity of hA and reduce virus replication in vitro (varečková et al, 2002, 2003aStropkovská et al, 2009). these MAbs, when passively applied, protected mice against lethal infection with IAvs of homologous or heterologous hA subtype (Gocník et al, 2007;Janulíková, unpublished data). In this study, we used two fragments of hA2 gp as immunogens, namely ehA2 and FP, the most conserved part of hA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new approaches to prevention providing a broad cross-protective immunity to influenza are focused on the conserved antigens of IAvs. A passive immunization with cross-protective antibodies has been successfully applied to several experimental models (Gocník et al, 2007;Throsby et al, 2008;Prabhu et al, 2009;Yoshida et al, 2009;Wang et al, 2010;corti et al, 2011;király et al, 2011). however, the passive immunization is limited to therapeutic purposes only and for effective prevention a new strategy of active immunization is required.…”
Section: Introductionmentioning
confidence: 99%
“…The HVC model allows us to investigate the effectiveness of new vaccines without relying on the old paradigm of anti-HA antibodies as the correlate of protection [23][24][25]. We recently chose an H3N2 influenza subtype to manufacture, rather than H1N1, given that this strain has the most substantial impact in terms of morbidity or mortality annually as described by the Centre for Disease Control [26].…”
Section: Influenzamentioning
confidence: 99%